A review of Buccipagoda Ponder, 2010 and descriptions of new species and a new genus (Gastropoda: Neogastropoda: Buccinoidea: Buccinidae). (2nd January 2019) - Marshall, Bruce A.; Walton, Kerry
ABSTRACT: This revision addresses two Southern Hemisphere genera in the family Buccinidae. Buccipagoda kengrahami (Ponder, 1982) and B. ponderi n. sp. are recognised from off southern Australia and B. achilles n. sp. from off New Zealand. Sagenotriton n. gen. is introduced for S. ajax n. sp. from off New Zealand, and S. bathybius (Bouchet & Warén, 1986) and S. bonaespei (Barnard, 1963) from off South Africa.